Butyric acid production from oilseed rape straw by Clostridium tyrobutyricum immobilized in a fibrous bed bioreactor. Issue 12 (December 2016) - Huang, Jin; Zhu, Han; Tang, Wan; Wang, Pu; Yang, Shang-Tian
Graphical abstract: Highlights: Oilseed rape (OSR) straw was alkaline pretreated and enzymatic hydrolyzed to sugars. C. tyrobutyricum in a fibrous bed bioreactor was used for butyrate fermentation. High butyrate titer, yield, and productivity were obtained in fed-batch fermentation. The fermentation process was stable for 10 consecutive repeated batches. The process can be used to economically produce butyrate in OSR straw biorefinery. Abstract: Butyric acid is an important specialty chemical with wide industrial applications, while economical production via feasible large-scale fermentation requires low-cost substrate and an efficient process. In this study, hydrolyzed oilseed rape (OSR) straw was used as an alternative carbon source for immobilized-cell fermentation of Clostridium tyrobutyricum to produce butyric acid. Compared to the free-cell fermentation, higher butyrate yield (0.43 g/g vs. 0.37 g/g), productivity (2.46 g/L/h vs. 0.93 g/L/h) and concentration (13.6 g/L vs. 11.6 g/L) were obtained with immobilized cells of C. tyrobutyricum in repeated-batch fermentation. Furthermore, fed-batch fermentation using pretreated OSR straw hydrolysate resulted in a high butyric acid concentration of 50.2 g/L, with yield of 0.38 g/g. Finally, the repeated batch fermentation was carried out, which achieved high butyrate yield and volumetric productivity during long-term operation. With desirable characteristics such as economic viability and competitiveness, as well as being environmentally friendly, the fermentation developed in this work should provide an efficient process for industrial production of butyric acid.